Nirmatrelvir/ritonavir and remdesivir against symptomatic treatment in high-risk COVID-19 outpatients to prevent hospitalization or death during the Omicron era: a propensity score-matched study - Sandra Rajme-López; Bernardo A. Martinez-Guerra; Carla M. Román-Montes; Karla M. Tamez-Torres; Andrea C. Tello-Mercado; Karen M. Tepo-Ponce; Zurisadai Segura-Ortíz; Abigail López-Aguirre; Orianlid del Rocío Gutiérrez-Mazariegos; Oswaldo Lazcano-Delgadillo; Rafael Nares-López; María F. González-Lara; et al. (Therapeutic Advances in Infectious Disease, 2024)
Background: Even though worldwide death rates from coronavirus disease 2019 (COVID-19) have decreased, the threat of disease progression and death for high-risk groups continues. Few direct comparisons between the available severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antivirals have been made. Objective: We aimed to compare two SARS-CoV-2 antivirals (nirmatrelvir/ritonavir and remdesivir) against all-cause hospitalization or death. Design: This is a propensity score-matched cohort study. Methods: We included all high-risk outpatients with COVID-19 in a tertiary referral center in Mexico City from 1 January 2022 to 31 July 2023. The primary outcome was all-cause hospitalization or death 28 days after symptom onset. The secondary outcome was COVID-19-associated hospitalization or death 28 days after symptom onset. Logistic regression analysis for characteristics associated with the primary outcome and a multi-group comparison with Kaplan–Meier survival estimates were performed. Results: Of 1566 patients analyzed, 783 did not receive antiviral treatment, 451 received remdesivir, and 332 received nirmatrelvir/ritonavir. The median age was 60 years (interquartile range: 46–72), 62.5% were female and 97.8% had at least one comorbidity. The use of nirmatrelvir/ritonavir was associated with an absolute risk reduction of 8.8% and a relative risk reduction of 90% for all-cause hospitalization or death. The use of remdesivir was associated with an absolute risk reduction of 6.4% and a relative risk reduction of 66% for all-cause hospitalization or death. In multivariable analysis, both antivirals reduced the odds of 28-day all-cause hospitalization or death [nirmatrelvir/ritonavir odds ratio (OR) 0.08 – 95% confidence interval (CI): 0.03–0.19, remdesivir OR 0.29 – 95% CI: 0.18–0.45]. Conclusion: In high-risk COVID-19 outpatients, early antiviral treatment with nirmatrelvir/ritonavir or remdesivir was associated with lower 28-day all-cause hospitalization or death.